FOOD SECURITY – WAYS OF INTEGRATION OF ECONOMIC PRIORITIES AND THE ECOLOGICAL IMPERATIVE - Onopriienko, Volodymyr; Onopriienko, Iryna; Kovalenko, Ihor; Kovalenko, Natalya; Volkova, Jeļena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The socio-economic problems of the agro-industrial complex of Ukraine and importance of the demographic factor in ensuring food security are determined. The factors of degradation of the environment in the agrosphere are indicated. The economic mechanism of nature use must be embedded in the economic system, and not be a distinct set of measures and tools aimed at addressing certain environmental problems. The main task of planning measures to ensure environmental safety is development of integrated target ecological programmes (national, regional, and internal management levels), which include measures for sustainable and safe nature management, oriented towards ecologically safe food products. The aim of the paper is to reveal the role of food security in integrating economic priorities and the ecological imperative. The following methods were used in the research: monographic, problem analysis, scientific induction and deduction methods, and adoption of a decision under conditions of uncertainty.